Forschungsdatenmanagement sozialwissenschaftlicher Umfragedaten Grundlagen und praktische Lösungen für den Umgang mit quantitativen Forschungsdaten - Jensen, Uwe; Netscher, Sebastian; Weller, Katrin (Verlag Barbara Budrich, 2019)
The book is based on practical requirements for the management of quantitative research data in small to medium-sized research projects in the social sciences, which generate and analyse data, save original data and archive and make them available for further use in the long term. In order to equip scientists with the tools to specifically meet these requirements, typical questions of data-based research projects are addressed on the basis of application cases and systematically processed with proven concepts of research data management. Overall, the book is a practical guide to documenting data-based research products (e.g. data files, measuring instruments, survey methods, analysis syntaxes) step by step, securing them professionally and making them available for subsequent use. In addition, the book highlights open questions and current challenges in dealing with research data. In the interest of scientifically and methodologically sound research data management, it also opens up perspectives for university education and research into the management of research data.